Administration of Δ9‐Tetrahydrocannabinol (THC) Post‐Staphylococcal Enterotoxin B Exposure Protects Mice From Acute Respiratory Distress Syndrome and Toxicity - Mohammed, Amira; Alghetaa, Hasan; Sultan, Muthanna; Singh, Narendra P.; Nagarkatti, Prakash; Nagarkatti, Mitzi (Frontiers in Pharmacology, 2020)
Acute Respiratory Distress Syndrome (ARDS) is a life-threatening complication that can ensue following Staphylococcus aureus infection. The enterotoxin produced by these bacteria (SEB) acts as a superantigen thereby activating a large proportion of T cells leading to cytokine storm and severe lung injury. Δ9Tetrahydrocannabinol (THC), a psychoactive ingredient found in Cannabis sativa, has been shown to act as a potent anti-inflammatory agent. In the current study, we investigated the effect of THC treatment on SEB-induced ARDS in mice. While exposure to SEB resulted in acute mortality, treatment with THC led to 100% survival of mice. THC treatment significantly suppressed the inflammatory cytokines, IFN-γ and TNF-α. Additionally, THC elevated the induction of regulatory T cells (Tregs) and their associated cytokines, IL-10 and TGF-β. Moreover, THC caused induction of Myeloid-Derived Suppressor Cells (MDSCs). THC acted through CB2 receptor as pharmacological inhibitor of CB2 receptors blocked the anti-inflammatory effects. THC-treated mice showed significant alterations in the expression of miRNA (miRs) in the lung-infiltrated mononuclear cells (MNCs). Specifically, THC caused downregulation of let7a-5p which targeted SOCS1 and downregulation of miR-34-5p which caused increased expression of FoxP3, NOS1, and CSF1R. Together, these data suggested that THC-mediated alterations in miR expression in the lungs may play a critical role in the induction of immunosuppressive Tregs and MDSCs as well as suppression of cytokine storm leading to attenuation of SEB-mediated lung injury.